Expériences migratoires et trajectoires familiales des réfugiés catholiques d’origine juive: - Nina Valbousquet (Diasporas: Circulations, Migrations, Histoire)
Drawing upon untapped Vatican archives for the period of World War II, this case study sheds light on a diplomatic agreement between the Holy See and Brazil granting 3,000 Brazilian visas for the emigration of European refugees considered "non-Aryan Catholics" (of Jewish descent) from 1939 to 1942. This article traces the journey of the refugees through Europe during the war and until their admission or deportation from Brazil. Pleas and nominative files uncover the refugees’ individual voices who faced family separations caused by racial and religious categorizations.